HUBUNGAN DUKUNGAN SUAMI DENGAN NYERI PERSALINAN DI UPT PUSKESMAS SELATBARU KECAMATAN BANTAN TAHUN 2019 - Heni Heri Yeni (Ensiklopedia of Journal, 2022)
Labor is an important event that a woman experiences in her life. Maternal mothers are difficult to adapt the labor pain can lead to incoordinated uterine contractions that may lead to extension labor periods and disturb of fetal well-being. This mean of research is determinethe relationship of husband support with labor pain in public health centre of Selatbaru, Bantan district. This research used correlational study design. The samples in this research are 35 mothers. The technique of sampling is total sampling. The instrument of this research usedquestionnaire. This research conducted by Chi Square statistical test. The results of the research conducted the majority of husband support in most categories did not support such as 28 peoples (80.0%) and the majority of most labor pain in the category of easy pain (60.0%). The results of statistical tests obtained with P-Value 0.022 which means less than α = 0.05. There is a relationship between husband support with labor pain. It is hoped that public health centre can provide information and identify labor problems related to labor pain and relate to improve the health services in maternal mothers by making a written policy about husband’s assist to maternal mother.